Nourishing futures: Assessing nutritional health among children under-five years of age belonging to a particularly vulnerable tribal community in Southern India - Sneha Deepak Mallya; Biju Soman; Srikanth Gouspure; Pavan Kumar Thatoju; Dinesh M. Nayak; Ashwini Kumar; Harpreet Kaur; Ranjitha S. Shetty (PLoS ONE, 2026)
Malnutrition is a major public health concern among tribal communities, where children face higher risk due to socio-economic disadvantages, poor healthcare access, and inadequate diets. Despite government programs, it persists, necessitating a focused assessment of its determinants. This study aimed to evaluate the nutritional status and its determinants among Koraga tribal children. A community-based cross-sectional study was conducted among children under-five years of age belonging to the Koraga community, a particularly vulnerable tribal group (PVTG) in southern Karnataka, India. Anthropometric measurements were taken, and data on socio-demographic characteristics, maternal and child health, and environmental conditions were collected using a structured proforma. Data analysis was performed using SPSS version 16.0 with logistic regression identifying factors associated with malnutrition. Among the 180 children included in the study, the median [interquartile range (IQR)] age of the children was 36 months (22.25, 46.00), and 52.2% were female. Low birth weight was reported in 40.2% of children, and 9.9% were currently anaemic. The study found a high prevalence of malnutrition among children under-five years of age, with 81.1% being stunted, 78.3% wasted, and 80.6% underweight. Multivariable analysis identified access to safe drinking water, maternal factors, nutritional factors, and dietary factors as significant contributors to undernutrition in this vulnerable population. The findings highlight the urgent need for targeted nutrition and health interventions in this PVTG. Strengthening maternal care, child feeding practices, sanitation, and healthcare access is essential to reduce malnutrition. A multi-sectoral approach is essential to break the cycle of undernutrition and improve overall child health outcomes.